2019
DOI: 10.1001/jamaoto.2018.2716
|View full text |Cite
|
Sign up to set email alerts
|

Association of Treatment Delays With Survival for Patients With Head and Neck Cancer

Abstract: IMPORTANCE Delays in the delivery of care for head and neck cancer (HNC) are a key driver of poor oncologic outcomes and thus represent an important therapeutic target. OBJECTIVE To synthesize information about the association between delays in the delivery of care for HNC and oncologic outcomes. EVIDENCE REVIEW A systematic review of the English-language literature in PubMed/MEDLINE and Scopus published between January 1, 2007, and February 28, 2018, was performed to identify articles addressing the assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
313
1
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 213 publications
(343 citation statements)
references
References 63 publications
7
313
1
7
Order By: Relevance
“…They found that a > 6-week interval between surgery and RT was detrimental in patients receiving the 7-week schedule and that completing the therapy in a cumulative time of > 13 weeks yielded a highly significantly lower local control and survival. The importance of DTI on survival results in our cohort, especially in the definitive SIB IMRT group is consistent with previously published data in which delayed initiation of radiation therapy resulted in decreased patients' outcomes [34]. The majority of patients (98%) in our cohort received their IMRT without chemoradiation related toxicity interruptions.…”
Section: Disease Controlsupporting
confidence: 91%
“…They found that a > 6-week interval between surgery and RT was detrimental in patients receiving the 7-week schedule and that completing the therapy in a cumulative time of > 13 weeks yielded a highly significantly lower local control and survival. The importance of DTI on survival results in our cohort, especially in the definitive SIB IMRT group is consistent with previously published data in which delayed initiation of radiation therapy resulted in decreased patients' outcomes [34]. The majority of patients (98%) in our cohort received their IMRT without chemoradiation related toxicity interruptions.…”
Section: Disease Controlsupporting
confidence: 91%
“…There will need to be a balance between recovery from chemotherapy and an increased risk of adverse survival outcomes from delaying surgery. 32 To the best of our knowledge, the available literature demonstrated a strong focus in other malignancies such as breast and gastric cancer, indicating that a 4-week interval may be a safe compromise. 33,34 Further studies on this topic in patients with HNC will help to guide the optimal timing of surgery and oncologic outcomes.…”
Section: Discussionmentioning
confidence: 98%
“…Treatment delay is associated with decreased disease control and survival, potentially driven by cancer stage progression or tumor cell repopulation after surgery prolonged treatment times . Although recent studies have analyzed treatment intervals for several different head and neck subsites, the impact of treatment delays in sinonasal cancer has yet to be elucidated.…”
Section: Introductionmentioning
confidence: 99%